The β‐link motif in protein architecture. Issue 8 (4th August 2021) - Leader, David P.; Milner-White, E. James
Abstract : The β‐link, which is a motif consisting of a G1β β‐bulge and a type II β‐turn, is shown to play the specific role in protein architecture of connecting a β‐sheet to another area of a protein in certain β‐sandwiches, small β‐barrels and β‐sheet/α‐helix proteins. Abstract : The β‐link is a composite protein motif consisting of a G1β β‐bulge and a type II β‐turn, and is generally found at the end of two adjacent strands of antiparallel β‐sheet. The 1, 2‐positions of the β‐bulge are also the 3, 4‐positions of the β‐turn, with the result that the N‐terminal portion of the polypeptide chain is orientated at right angles to the β‐sheet. Here, it is reported that the β‐link is frequently found in certain protein folds of the SCOPe structural classification at specific locations where it connects a β‐sheet to another area of a protein. It is found at locations where it connects one β‐sheet to another in the β‐sandwich and related structures, and in small (four‐, five‐ or six‐stranded) β‐barrels, where it connects two β‐strands through the polypeptide chain that crosses an open end of the barrel. It is not found in larger (eight‐stranded or more) β‐barrels that are straightforward β‐meanders. In some cases it initiates a connection between a single β‐sheet and an α‐helix. The β‐link also provides a framework for catalysis in serine proteases, where the catalytic serine is part of a conserved β‐link, and in cysteine proteases, including M pro of human SARS‐CoV‐2, in which two residues of the active site are located in a conserved β‐link.